Excluding the queer unwanted: Perspectives from older LGBTQ+ adults in New Zealand. Issue 4 (2nd October 2021) - Betts, David
Abstract: This article focuses on the community connections of older people with diverse sexual, gender, and/or sex characteristics in New Zealand. Specifically, it is reporting on how access to social spaces is filtered through perceptions of who is welcome in lesbian, gay, bisexual, transgender, and queer (LGBTQ+) spaces. Thirty-one qualitative semi-structured interviews were conducted with older adults (ages 60–80) who were part of LGBTQ+ communities. These interviews addressed the topics of social connection, wellbeing, and identity. The findings indicated that identity-based exclusion resulted in disconnection from LGBTQ+ social spaces, with participants reporting both active and passive actions that positioned these spaces for specific individuals, resulting in a group that has previously been described in research as the queer unwanted.